Strong Association of the Myriad Discrete Speckled Nuclear Pattern With Anti-SS-A/Ro60 Antibodies: Consensus Experience of Four International Expert Centers - Röber, Nadja; Dellavance, Alessandra; Ingénito, Fernanda; Reimer, Marie-Luise; Carballo, Orlando Gabriel; Conrad, Karsten; Chan, Edward K. L.; Andrade, Luis E. C. (Frontiers in Immunology, 2021)
Introduction: The morphological patterns in indirect-immunofluorescence assay on HEp-2 cells (HEp-2/IFA) reflect the autoantibodies in the sample. The International Consensus on ANA Patterns (ICAP) classifies 30 relevant patterns (AC-0 to AC-29). AC-4 (fine-speckled nuclear pattern) is associated to anti-SS-A/Ro, anti-SS-B/La and several autoantibodies. Anti-SS-A/Ro samples may contain antibodies to Ro60 and Ro52. A variation of AC-4 (herein designated AC-4a), characterized by myriad discrete nuclear speckles, was reported to be associated with anti-SS-A/Ro. The plain fine-speckled pattern (herein designated AC-4b) seldom was associated with anti-SS-A/Ro. This study reports the experience of four expert laboratories on AC-4a and AC-4b. Methods: Anti-Ro60 monoclonal-antibody A7 was used to investigate HEp-2/IFA pattern. Records containing concomitant HEp-2/IFA and SS-A/Ro tests from Durand-Laboratory, Argentina (n=383) and Fleury-Laboratory, Brazil (n=144,471) were analyzed for associations between HEp-2/IFA patterns and disease-associated autoantibodies (DAA): double-stranded DNA, Scl-70, nucleosome, SS-B/La, Sm, U1-RNP. 301 samples from Dresden Technical University (TU-Dresden), Germany, were assayed for HEp-2/IFA and DAA. Results: Monoclonal A7 recognized Ro60 in western blot and immunoprecipitation, and yielded the AC-4a pattern on HEp-2/IFA. Analyses from Durand-Laboratory and Fleury-Laboratory yielded compatible results: AC-4a was less frequent (8.9% and 2.7%, respectively) than AC-4b (26.1% and 24.2%) in HEp-2/IFA-positive samples. Reactivity to SS-A/Ro occurred in 67.6% and 96.3% of AC-4a-pattern samples against 23% and 6.8% of AC-4b-pattern samples. Reciprocally, AC-4a occurred in 24% and 47.1% of anti-SS-A/Ro-positive samples, and in 3.8% and 0.1% of anti-SS-A/Ro-negative samples. AC-4a pattern occurred in 69% of 169 anti-SS-A/Ro-monospecific samples and in 4% of anti-SS-A/Ro-negative samples from TU-Dresden. In all laboratories, coexistence of anti-SS-B/La, but not other DAA, in anti-SS-A/Ro-positive samples did not disturb the AC-4a pattern. AC-4a was predominately associated with anti-Ro60 antibodies. Conclusions: This study confirms the association of AC-4a pattern and anti-SS-A/Ro in opposition to AC-4b pattern. The results of four international expert laboratories support the worldwide applicability of these AC-4 pattern variants and their incorporation into ICAP classification under codes AC-4a and AC-4b, respectively. AC-4 pattern should be maintained as an umbrella pattern for cases in which one cannot discriminate AC-4a and AC-4b patterns. The acknowledgment of the AC-4a pattern should add value to HEp-2/IFA interpretation.